INTEGRATION OF ALLOPHONE CHILDREN IN LEARNING FRENCH AS A FOREIGN LANGUAGE: A COMPARISON OF THE EXPERIENCES OF FRANCE AND UZBEKISTAN (2020–2024) - Tamara Kavilova (Western European Studies, 2025)
The article examines the problem of integrating allophone children in learning French as a foreign language in the context of inclusive education. A comparative analysis of the approaches implemented in France and Uzbekistan in the period from 2020 to 2024 is conducted. The main integration problems are identified, such as the language barrier, cultural differences and lack of pedagogical training. Measures to improve the situation are proposed, including the development of bilingual programs, the use of digital technologies and increased funding. The article emphasizes the importance of international cooperation and the adaptation of the successful experiences of both countries
Keywords: inclusive education; allophone children